Treatment and high value utilization of glutamic acid wastewater. Issue 10 (1st November 2022) - Yu, Fupeng; Zhao, Chen; Su, Le; Zhang, Song; Sun, Xin; Li, Kunlun; Yue, Qiulin; Zhao, Lin
Abstract: Glutamate wastewater has a high yield in the world and is difficult to be treated due to its high acidity, high COD (chemical oxygen demand, reflecting the pollution degree of reduced substances in the water) and high ammonia nitrogen characteristics. In this study, Bacillus licheniformis M 2020051 was used to treat organic wastewater to ferment polyglutamic acid, which reduced the pollution of industrial wastewater and produced polyglutamic acid at a low cost. Firstly, a strain with high salt tolerance and high polyglutamic acid production was isolated from saline soil, and the mechanism of salt tolerance and polyglutamic acid production were also analyzed. Then Single-factor experiment and Response surface methodology (RSM) were used to determine the appropriate fermentation conditions to achieve maximum γ-polyglutamic acid production. After optimization, the yield of polyglutamic acid was increased to 6.91 g·L −1 by shaking fermentation, an increase of 7.13%. Finally, the agronomic experiments were carried out, and the results showed that γ-polyglutamic acid could significantly increase the germination rate of corn seeds and the growth of rapeseed. These studies will lay the foundation for reducing industrial wastewater pollution and exploring the production model of γ-polyglutamic acid.